Національні морегосподарські інтереси україни в Чорноморсько-Азовському басейні - Burkinskyi, Boris; Stepanova, Kateryna (Dr. Viktor Koval, 2017)
Introduction. Maritime economy is one of the most important factors of economic growth and national security. Prior to the post-Soviet stage of development, a high level of "maritime maturity" was achieved in Ukraine. Well-developed and diversified maritime economic complex of Ukraine included maritime transport, fisheries, shipbuilding and ship repair, marine engineering, offshore gas industry, seaports, sea recreation with cruise fleet of international standards, etc. During the last years Ukraine has lost most of its maritime potential. The renewal of maritime economy and recovery of the maritime complex became one of the most important national interests of Ukraine. Aim and tasks. The paper aims to analyse the problems of maritime complex of Ukraine and formulate national maritime interests of Ukraine under new geopolitical and economic conditions in the Black Sea region. Research results. In order to discuss the maritime interests of Ukraine was proposed a fractal model which considers maritime interests in the following dimensions: economy, geopolitics, environment, military-defence. As the strategic economic interests of Ukraine are considered: use of marine natural resources that can contribute to economic growth; development of transport and communication in the Black Sea-Azov basin and other areas of the World Ocean; development of recreational and tourism potential of Ukrainian Black Sea coast; marine energy development. Considering the geopolitical aspects, national interests include maintenance of the territorial integrity of Ukraine, development of a system of sustainable strategic, political and economic cooperation. Environmental aspect of maritime interests of Ukraine includes rational use of natural resources, greening of economic activities in costal areas, environmental management, reproduction of biological resources and protection of biodiversity of the Black and Azov Seas. In recent years the military-defence aspect of national interests takes on special significance. It includes, first of all, the effective realization of the defence strategy at the southern borders and development of the Naval Forces of Ukraine. Conclusions. National maritime interests of Ukraine were discussed from economic, geopolitical, environmental and military-defence points of view. One of important strategic interests of Ukraine is to ensure stability and protection of the regional security in the Black Sea-Azov region, which has become an arena of complex geopolitical and geoeconomic contradictions in the context of growing economic development trends in the region, transboundary and international problems.